2015
DOI: 10.1007/s10517-015-3013-7
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative and Migration Activity of JEG-3 Trophoblast Cell Line in the Presence of Cytokines

Abstract: TNFα inhibited proliferation and did not inhibit migration JEG-3 trophoblast cells, IL-1β stimulated both cell proliferation and migration, IL-6 and IL-8 stimulated only cell migration, IFNγ has either stimulating or inhibitory effect on proliferation of trophoblast cells depending on its concentration. Cytokines IL-10 and IL-4 stimulated only migration of trophoblast cells. VEGF, PlGF, and TGFβ stimulated both proliferation and migration, and bFGF only migration of trophoblast cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…There is a number of IL-1b sources in the uteroplacental contact zone: trophoblast, uNK cells, and others [2]. Previously, we showed IL-1b ability to enforce JEG-3 cells proliferation in 10 U/mL concentration [3]. Here, we observed no cell mortality growth in this concentration while exceeded concentrations lead to trophoblast mortality growth (Figure 1(D)).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…There is a number of IL-1b sources in the uteroplacental contact zone: trophoblast, uNK cells, and others [2]. Previously, we showed IL-1b ability to enforce JEG-3 cells proliferation in 10 U/mL concentration [3]. Here, we observed no cell mortality growth in this concentration while exceeded concentrations lead to trophoblast mortality growth (Figure 1(D)).…”
Section: Discussionsupporting
confidence: 58%
“…We showed that IFNc in 1000 U/mL concentration enforced trophoblast mortality but this effect could not be spotted for 40 and 400 U/mL concentrations (Figure 1(D)). We have shown earlier that it was in 40 and 400 U/mL concentrations that IFNc enforced JEG-3 cells proliferation [3].…”
Section: Discussionmentioning
confidence: 86%
“…Both models had the same vasoactive factors being increased by GBS: IL-6 and CXCL-8. Although IL-6 regulation of trophoblast cell migration is still debated ( Champion et al, 2012 ; Sokolov et al, 2015 ), its roles in vascular dysfunction are well-established. IL-6 has increased levels in preeclamptic patients ( Lockwood et al, 2008 ) and promotes thrombogenesis, increased expression of endothelial adhesion molecules, and vascular permeability ( Roldán et al, 2003 ), increased vascular fibrosis, immune cell recruitment, endothelial activation, and its further dysfunction ( Didion, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The levels of the secreted MMP-2 and MMP-9 were significantly elevated by IL-8 treatment, as was the trophoblast expression of integrin α5 and β1, compared to the non-treated cells [ 24 , 26 ]. Furthermore, the viability and proliferation of HTR-8/SVneo cells increased following IL-8 treatment [ 26 , 54 ], as well as HTR-8/SVneo- and JEG-3-cell migration [ 26 , 55 ]. IL-8 has also been designated as one of the key EVT-secreted factors involved in spiral artery remodeling [ 45 ].…”
Section: Il-6 and Il-8 In A Healthy Pregnancymentioning
confidence: 99%